perbandingan metode fitoremidiasi antara tanaman kayu apu (pistia stratiotes) dengan eceng gondok (eichhornia crassipes) dalam menurunakan kadar amoniak (studi kasus limbah cair tahu) - Fuadi, Ilham; Arifin, Arifin; Hamzani, Sulaiman; Zubaidah, Tien (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Tofu industries produce wastewater containing ammonia, which has the potential to pollute the environment. One method of treating such wastewater is phytoremediation, which involves the use of aquatic plants to absorb or reduce pollutant concentrations. This study compares the effectiveness of two types of aquatic plants, namely water lettuce (Pistia stratiotes) and water hyacinth (Eichhornia crassipes), in reducing ammonia levels in tofu wastewater. This research employed a quasi-experimental design with a pre-test and post-test approach using two comparative treatments. The samples consisted of 12 treatment units with water lettuce, 12 units with water hyacinth, and 4 control units without treatment. Data analysis was conducted using the Wilcoxon test. The results showed that the control group experienced a 27.3% reduction in ammonia levels. The water lettuce groups with weights of 300, 600, and 900 grams showed reductions of 80.3%, 82.7%, and 74.1%, respectively. Meanwhile, the water hyacinth groups demonstrated reductions of 74.5%, 77.7%, and 86.4%, respectively. Statistical analysis yielded a p-value of 0.001 (p < 0.05), indicating a significant difference between pre- and post-treatment conditions. In conclusion, both water lettuce and water hyacinth were effective in reducing ammonia levels in tofu wastewater, with the highest effectiveness achieved by water hyacinth at a weight of 900 grams.